SOLUSI ALTERNATIF DAN KONSTRUKTIF UNTUK MENGATASI PROBLEMATIKA POSISI PEREMPUAN KARIR - Suparta, Suparta (NOURA: Jurnal Kajian Gender dan Anak, 2017)
Based on Islamic history, even if reviewed 1400 years ago at the time of the Prophet. To prove that women’s roles and positions are very noble and even glorified. How not, to the extent to prove that women have a great position there is a hadith that states that heaven is in the soles of the mother’s feet. Even the position of man in the presence of Allah never seen from the type of man or woman, but the see is piety. It provides an excellent opportunity for women to be able to work out anything as long as it does not violate the shariah. Not a few women are very prominent knowledge and become role models and references of many male characters. Aisha, the wife of the Prophet Muhammad, is a brilliant, intelligent and critical person. As-Sayyidah Sakinah, Princess al-Husayn ibn Ali ibn Abi Talib, Asy-Shaykh al-Shuhrah who has the blessing of "Fakhr an-Nisa" (pride of women) is the teacher of Imam Syafi’i and many others.